1997
DOI: 10.1007/bf01622286
|View full text |Cite
|
Sign up to set email alerts
|

Population-based geographic variations in dxa bone density in Europe: The evos study

Abstract: Abstract. The purpose of this study was to investigate variations in bone density between 16 European populations, 13 of which were participants in the European Vertebral Osteoporosis Study (EVOS). Men and women aged 50-80 years were recruited randomly from local population registers, stratified in 5-year age bands. The other three centres recruited similarly. Random samples of 20-100% of EVOS subjects were invited for dual-energy X-ray absorptiometry (DXA) densitometry of the lumbar spine and/or proximal femu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
5
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 31 publications
5
87
5
5
Order By: Relevance
“…The variation was larger than regional variation found in the U.S. [18], but smaller than geographic variation found within Norway, Mexico, Japan [19][20][21] or across Europe [22]. As expected, regional variation in the prevalence of osteoporosis (as defined by BMD T-scores≤−2.5) was related to underlying differences in the distribution of BMD.…”
Section: Discussionsupporting
confidence: 54%
“…The variation was larger than regional variation found in the U.S. [18], but smaller than geographic variation found within Norway, Mexico, Japan [19][20][21] or across Europe [22]. As expected, regional variation in the prevalence of osteoporosis (as defined by BMD T-scores≤−2.5) was related to underlying differences in the distribution of BMD.…”
Section: Discussionsupporting
confidence: 54%
“…However this would only be of major importance where treatment decisions are made on the basis of a fixed T-score threshold as in the UK [12]. In previous work it has been observed that there are quite substantial between centre differences in BMD in older populations of men and women [6] and that rates of bone loss or gain differ between centres [13]. The between country and between centre differences in mean BMDs described in this paper will allow the study of whether these differences are apparently growing over time (implying an impact of ecology on the evolution of BMD) or whether they are constant across the range of adult ages in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…This was done as described by Pearson et al [3], Kalender et al [5], and Lunt et al [6]. The minimum acceptable data for inclusion in the study was BMD at one measurement site (from femoral neck, trochanter, or L2-L4 spine), age, weight, and height at/or near the scan date.…”
Section: Dxa Proceduresmentioning
confidence: 99%
“…Tatt vitamin D-statusen i betraktning var dette et overraskende funn. På den annen side er nordmenn blant de med høyest bruddrate (14-16) og lavest verdi av bentetthet som er rapportert internasjonalt (17).…”
Section: Diskusjonunclassified